Acridino[2, 1, 9, 8‐klmna]acridine Bisimides: An Electron‐Deficient π‐System for Robust Radical Anions and n‐Type Organic Semiconductors. Issue 25 (17th May 2021) - Tajima, Keita; Matsuo, Kyohei; Yamada, Hiroko; Seki, Shu; Fukui, Norihito; Shinokubo, Hiroshi
Abstract: We report the synthesis and properties of acridino[2, 1, 9, 8‐ klmna ]acridine bisimide (AABI), a nitrogen‐doped anthanthrene with two imide functionalities. AABI exhibits excellent electron affinity as evident by its low‐lying LUMO level (−4.1 eV vs. vacuum). Single‐electron reduction of one AABI derivative afforded the corresponding radical anion, which was stable under ambient conditions. Photoconductivity measurements suggest that the intrinsic electron mobility of an N ‐phenethyl AABI derivative obeys a band‐transport model. Accordingly, an electron mobility of 0.90 cm 2 V −1 s −1 was attained with the corresponding single‐crystal organic field‐effect transistor (OFET) device. The vacuum‐deposited OFET device consisting of a polycrystalline sample exhibited high electron mobility of up to 0.27 cm 2 V −1 s −1 even in air. This study demonstrates that dual incorporation of both imide substituents and imine‐type nitrogen atoms is an effective strategy to create novel electron‐deficient π‐systems. Abstract : Acridino[2, 1, 9, 8‐ klmna ]acridine bisimides (AABIs), nitrogen‐doped anthanthrenes with two imide functionalities (see structure), were found to exhibit excellent electron affinity, affording an air‐stable radical anion. The intrinsic electron mobility of one derivative obeyed a band‐transport model. Accordingly, the corresponding single‐crystal organic field‐effect transistor device showed high electron mobility of 0.90 cm 2 V −1 s −1 .